2009
DOI: 10.1128/aac.01290-08
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of LB80331 and LB80317 following Oral Administration of LB80380, a New Antiviral Agent for Chronic Hepatitis B (CHB), in Healthy Adult Subjects, CHB Patients, and Mice

Abstract: LB80380, a dipivoxil ester prodrug of LB80331 (metabolite, LB80317), is a novel antiviral agent for chronic hepatitis B (CHB). The pharmacokinetics of LB80331/LB80317 were evaluated in two clinical studies and a study with mice. The clinical studies were dose-escalating pharmacokinetic studies with six healthy subjects per single-dose group and six CHB patients per repeated-dose group. The mouse study was designed to measure the amounts of the phosphorylated portions of LB80331 and LB80317 in the liver. In hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…85 Interestingly, the absorption of the prodrug was delayed by high fat diet. 85 Initial data in mice showed that ca. 40% of the active metabolite was generated in the liver.…”
Section: Besifovirmentioning
confidence: 99%
“…85 Interestingly, the absorption of the prodrug was delayed by high fat diet. 85 Initial data in mice showed that ca. 40% of the active metabolite was generated in the liver.…”
Section: Besifovirmentioning
confidence: 99%
“…The t 1/2 is much longer (45 -62 hours) compared to LB80331. The AUC and C max between LB80317 and LB80331 correlate strongly (r=0.9181 and r=0.8998, respectively) [12]. The pharmacokinetic parameters of LB80331 and LB80317 following single dose and multiple doses administration are summarized in Table 2 and Table 3, respectively.…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 98%
“…The pharmacokinetics of besifovir in human were illustrated in two phase I studies [11,12]. Since LB80380 is a prodrug and is not detected in plasma, its metabolites namely LB80331 (intermediate metabolite) and LB80317 (the active metabolite) were measured.…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 99%
“…Clinical trials with clevudine, a newer pyrimidine nucleoside that was already approved in some Asian countries, have been stopped in 2009 because myopathy was reported in a number of patients [35][36][37]. Prodrugs that are selectively metabolized and activated in the liver, as for example, LB80380 (similar to adefovir and tenofovir) are currently being tested [38][39][40][41]. Apart from that, an acyclic pyrimidine nucleoside phosphate named PMEO-DAPym represents the prototype compound of a novel class of pyrimidine acyclic nucleoside phosphonates that are recognized as a purine nucleotide [42].…”
Section: Nucleos(t)ide Analogues (Nucs)mentioning
confidence: 99%